2019
DOI: 10.1016/j.compositesa.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Comparative experimental and numerical analysis of bending behaviour of dry and low viscous infiltrated woven fabrics

Abstract: Wet compression moulding (WCM) provides high-volume production potential for continuous fibre-reinforced composite components via simultaneous draping and infiltration. Experimental and theoretical investigations proved strong mutual dependencies between resin flow and fabric deformation, which are not fully understood yet. This limits development of suitable process simulation methods and applies in particular for the characterisation of infiltrated bending behaviour-essential for an accurate prediction of dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…At a curvature of 0.01 mm −1 , the width-normalized moment is approximately 50% higher for the RBT compared to the FCT and VCT. Similar discrepancies were observed by Poppe et al [11] who gave two main explanations: 1) Sliding friction in the clamps of the RBT and 2) a reduced specimen thickness of the FCT and VCT near the fixation due to the clamping force. It should be remarked, though, that for FCT, VCT and RBT, the slopes, i.e.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…At a curvature of 0.01 mm −1 , the width-normalized moment is approximately 50% higher for the RBT compared to the FCT and VCT. Similar discrepancies were observed by Poppe et al [11] who gave two main explanations: 1) Sliding friction in the clamps of the RBT and 2) a reduced specimen thickness of the FCT and VCT near the fixation due to the clamping force. It should be remarked, though, that for FCT, VCT and RBT, the slopes, i.e.…”
Section: Resultssupporting
confidence: 83%
“…The test was denoted the rheometer bending test (RBT). See also the study by Poppe et al [11] that features a comparison between the RBT and the FCT for a low viscous infiltrated fabric. The authors reported that the RBT in general would predict a higher bending stiffness than the FCT which among others was explained by sliding friction of the specimen in the moving clamp.…”
Section: Introductionmentioning
confidence: 99%
“…The rotation bending test allows for high-curvature deformation with rate and temperature dependence, high data acquisition accuracy, and a small test environment to perform test programs in a time-efficient manner. Several CFRTP materials have already been characterized using this approach by several research groups for material modeling and validation purposes, including published data [14,18,[22][23][24][25]. Typical bending moments for single-tape specimens at processing temperatures are in the range of 10 −4 Nm.…”
Section: Introductionmentioning
confidence: 99%
“…State of the art forming simulation approaches mainly apply conventional two-dimensional shell approaches [5] to efficiently model the deformation of thin fibrous reinforcements, since they allow for high aspect ratios while still accurately describing the membrane and bending behaviour. However, those approaches cannot model out-of-plane compaction, which is an important forming mechanism to predict local fibre volume contents [6] and influences the permeability of the reinforcement during processes such as wet compressions moulding [7,8]. To predict these effects and the final thickness of the part, a three-dimensional FE-formulation is necessary.…”
Section: Intr Introduction Oductionmentioning
confidence: 99%